Variability of laminar debitage in the second Mesolithic and early Neolithic in the north of France (7th and 6th millennium BCE) - Allard, Pierre (Journal of Lithic Studies, 2017)
This paper presents an overview of the knapping techniques of the Second Mesolithic and Early Neolithic during the 7th and 6th millennium in Northern France. This period is characterised by the emergence of new armatures - the trapezes - and of new techniques of prismatic blade production that show discontinuation from the preceding technical traditions. Basically, if we admit that the success of these new technical practices is linked to their intrinsic qualities (higher regularity and parallelism of the blanks, control of the gesture and of the impact point as well as higher productivity), this can explain that the investment into the production focuses on the blanks rather than on the processes of retouch. This paper presents the current state of the data regarding the knapping techniques and their distribution. This analysis is based on the technological approach aiming at characterizing the types of production and the techniques of percussion. At the current state of analysis, only indirect percussion (punch) knapping technique is observed in the northern and western part of the area. Nonetheless, a more detailed study is still required in order to better describe distinct, very regular bladelet productions made from small-sized cores (eastern part of France). With respect to the geographical extension of the considered area, it can be stated that technological studies are still indigent. The debitage of L’Essart A seems to correspond to the common thread of the Late Mesolithic types of production by indirect percussion. However, some well-documented areas allow the perception of different types of indirect percussion which involves variants independent from the raw material which become apparent in the knapping procedures. This is the case of the the Retzian which is clearly opposed to the Teviecian through the procedures of systematic core preparation by microfacetting but also through the outstanding stylistic unity of the trapeze types. Debitage on the edge of a flake for the creation of blade surfaces seems for instant restricted to the Tardenoisian in a wider sense which means an area extending from the Paris Basin to Belgium. The chronological dimension is a crucial factor that has to be incorporated into the analysis. With regard to indirect percussion, an expanded chronological framework of the lithic assemblages would permit to understand whether the different variants are synchronous or diachronic. New discoveries gave us a better idea of the beginning of indirect percussion in Paris basin (around 6200 cal BC according to the dating of the grave of Cuiry-lès-Chaudardes). The study of this « complex » of trapeze industries encompasses several levels of observation that have to be refined. The phenomenon is considered here globally. But as we have seen, some well defined entities seem to emerge within this complex. These are preliminary results for the moment and an interpretation that makes sense has yet to be made for these different practices. The typological evolution of trapezes and derived triangles has to be incorporated into the results obtained from the technological approach in order to determine whether the stylistic and technological entities can be correlated. The precise intersection between the stylistic entities and the technological variants assumed here has to be demonstrated. It will probably be possible to subdivide this complex in order to better understand its evolution.